Antimicrobial Activity of TiO2 Coatings Prepared by Direct Thermophoretic Deposition of Flame-Synthesized Nanoparticles. (27th December 2016) - De Falco, Gianluigi; Porta, Amalia; Del Gaudio, Pasquale; Commodo, Mario; Minutolo, Patrizia; D'Anna, Andrea
ABSTRACT: This study reports the development of a one-step method for the production of antimicrobial protective coatings for aluminum surfaces with titania nanoparticles. An aerosol flame synthesis system was used to produce monodisperse, ultra-fine TiO2 nanoparticles, which were directly deposited by thermophoresis onto plates of aluminum alloy by means of a rotating disc. Fuel-lean reactor conditions were used to synthesize pure anatase nanoparticles of 3.5 nm in diameter. Substrates were mounted onto the rotating disc that repetitively passes through the flame. Convection due to the rotational motion cooled the substrates, on which particles were deposited as films by thermophoresis. Such a system allowed to obtain submicron coatings of different thickness, by varying the total time of deposition. The antimicrobial activity of TiO2 coatings was tested against the Gram positive bacterium Staphylococcus aureus . To determine the inhibition of biofilms formation, microbes were plated on TiO2 coatings and a semi-quantitative colorimetric assay was performed using crystal violet. The tests showed that the TiO2 coating obtained with tdes =10 s inhibits up to 70-80% Staphylococcus aureus biofilm formation, and the inhibition of biofilms formation was confirmed by means of Scanning Electron Microscopy observation. Also, the antimicrobial properties of the coatings was enhanced by irradiating the samples in the UV region. The results of the present work are promising for using titania films as protective coatings for applications where an antimicrobial activity is required.